Determination of Water Quality Status with the Storet Method in Raja Lake, Indragiri Hulu, Riau Province - Sri Rahayu; Nur El Fajri; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract                 Raja Lake in Rengat City has various social, economic and ecological functions such as tourism and fishing. These various activities produce pollutants that will affect water quality. This study aims to determine the status of water quality in Raja Lake. The study was conducted in August 2021. Water samples were taken at 3 stations with 3 replications. The water quality parameters measured were temperature, TSS, TDS, pH, COD, BOD5, fat oil, sulfur, detergent and total coliform. The measurement results show that the COD are higher than the standards issued by the Indonesian government. Temperatures ranged from 29-31oC, pH 6, BOD5with a value of 2.2 – 3.4 mg/L, TSS 11 - 23 mg/L, TDS 46 - 87 mg/L, sulfur 0.0001 – 0.012 mg/ L, fat oil 106 - 188 µg/L, detergent 79 - 183 µg/L and total coliform 15-28 MPN/100 ml. Based on the data obtained, it can be concluded that Raja Lake is classified as moderately polluted (scores range from  -4 to -8). Keywords: Raja Lake, Storet Method, Water Quality, Water Quality Status